The Italian perspective on the use of Big Data in Sociological Field: Implications, Empirical Findings and an Impact Analysis on the Discipline - Michela Cavagnuolo (Culture e Studi del Sociale)
Digital development has invested predominantly in all fields of society: the field of sociology and in general the field of social sciences are not exempt. Starting from these considerations, the social scientist is called to integrate everything within his studies with technological innovations and new tools that modifies and innovates the typical toolbox of the study. This change creates a context of strong interdiscipline. An analysis of the changes and impact of the use of Big Data within the social sciences and how they modify the work of the social scientist therefore becomes necessary.